2021
DOI: 10.18502/jchr.v10i1.5829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality of Bread; Based on the Amount of Salt and Baking Soda Consumption

Abstract: Introduction: Bread is an unavoidable food ingredient in Iranian meals. Given the relationship between salt and baking soda and several diseases, this study aimed to investigate the role of bread and its effect on increasing additives (salt and baking soda) and comparing them to standards. Methods: In this cross-sectional study, all bakeries (95 bakeries) of Garmsar county were selected and sampled from consumed bread (Taftoon; 125, Barbari; 168, Lavash; 48 and, Sangak; 22 samples) and were sent to the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A low compliance rate with the latest national standard for salt in bread was also found in samples (n=59) taken in 95 bakeries in the county of Garmsar in Northern Iran, with only 16.3% containing <1% of salt. The mean salt content was 1.37% with variations between the four bread types analysed (Abolli et al, 2021). In another study, the salt content of various industrially and nonindustrially produced processed foods including tomato paste and sauces, canned vegetables, pickles and nuts was evaluated, with samples taken in 2016 and 2018 to compare the findings.…”
Section: Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A low compliance rate with the latest national standard for salt in bread was also found in samples (n=59) taken in 95 bakeries in the county of Garmsar in Northern Iran, with only 16.3% containing <1% of salt. The mean salt content was 1.37% with variations between the four bread types analysed (Abolli et al, 2021). In another study, the salt content of various industrially and nonindustrially produced processed foods including tomato paste and sauces, canned vegetables, pickles and nuts was evaluated, with samples taken in 2016 and 2018 to compare the findings.…”
Section: Environmentmentioning
confidence: 99%
“…A study in Iran found that lower use of salt in bread was associated with a higher use of baking soda to account for the consequent problems with bread texture and to compensate for the low quality of wheat flour. Baking soda has been found to reduce the absorption of minerals like calcium and iron, promote the uptake of heavy metals, and destroy vitamins like thiamine and riboflavin (Abolli et al, 2021). Bakers often lack awareness about the negative effects of high salt intake and the technical know-how to reduce salt content in bread without loss of quality.…”
Section: Future Needs and Further Steps In Food Reformulationmentioning
confidence: 99%